Common ritualistic myths during pregnancy in Northern India - Choudhary, Ramesh; Gothwal, Sunil; Nayan, Swati; Meena, B. S. (International Journal of Contemporary Pediatrics, 2017)
Background: The development in science and technology has helped us to overcome the superstitions associated with pregnancy to some extent. Objective of present study was to record information about common ritualistic myths during pregnancy and after baby birth. Methods: It was a cross sectional observational study conducted in a tertiary care center. Information was collected from 200 admitted women who delivered in last 3 days with direct questions to mother. Results: Total 180 (90%) women were following the ritualistic myths. Mean age and mean parity was 30.1 years and 2.8 respectively. Sixty five percent women were belonging from rural background. Religion distribution was as follows 144 Hindu, 40 Muslim and 16 were others. Prevalence of the myths was 136 (94.4%), 32 (80%), 12 (75%) in Hindu, Muslim and other religions respectively. An inverse relation was observed between education level and acceptance of myth. Conclusions: Ritualistic myths during pregnancy and after birth were more common with low literacy, rural background and in Hindus.